Light & darkness late modernism and the JW Power Collection - Stephen, Ann (Power Publications, 2021)
"Light and Darkness is a revelation. The first project to explore the JW Power Collection of contemporary art in its new home at the University of Sydney's Chau Chak Wing Museum, this anthology and exhibition reveals many works not seen for decades. Under curator Ann Stephen's deft editorial hand, some 70 works from the 1500 in the Power Collection point to key directions -- the wonderful luminal and kinetic works from the late 1960s; the diversity of the 1970s, ranging from Jasper Johns to On Kawara; the turn in the 1980s to collecting art from Australia and New Zealand. All these works are illuminated by fresh research, in probing essays showing that scholarship is the flame that sustains all museums." -- Julie Ewington, Independent writer, curator and broadcaster, Sydney. Former Head of Australian Art, QAOMA, Brisbane
Impressum: Published in association with the exhibition "Light and Darkness", Chau Chak Wing Museum, University of Sydney, 18 September 2021. - Genaue Ausstellungsdaten ermittelt: until 27 November 2022
Keywords: Power, John Wardell -- 1881-1943; Chau Chak Wing Museum; Geschichte 1960-1990; Kunst; Sammlung; Art, Modern / 20th century / Private collections / Australia / Exhibitions; Art, Modern / 20th century / Exhibitions; Art, Australian / 20th century / Exhibitions; Ausstellungskatalog -- Chau Chak Wing Museum -- 18.09.2021-27.11.2022 -- Sydney